Implementation of an Enterprise Resource Planning System to Improve the Productivity of Cash Register Collections of an Important Clinic in the City of Lima - Infantes Loo, Juan Faustino (2022)
The purpose of this study is to show the results obtained after the implementation of an enterprise resource planning system in an important clinic in the city of Lima. Quantitative and qualitative techniques were applied to determine the improvements or benefits that arose from implementation. The results are shown in tables and graphs that were prepared based on the information obtained from the users of the ERP system/cash register module. It is concluded that a better control of cash register collections contributes to better productivity performance and better customer service.